Investigating Traceability Costs and Benefits in Food Supply Chain: Case Study in Serang City, Indonesia - kiki khoifin; Suthep Nimsai (International Journal of Supply Chain Management, 2018)
As a consequence of the increased of food demand. Food industry had been considered as a crucial player to implement food safety from farm to fork. Traceability is recognized as one of the critical instruments for assuring food safety and quality. Further, in business realm the queries had been arisen from practitioners about perceiving costs and benefits of traceability implementation. This study used sample of 30 food industries in Serang city, Indonesia, and analysed through path analysis. The result shown that perceiving the traceability both costs and benefits were relied on the traceability level implemented. Further, the respondents paid attention into traceability costs in terms of material and label/packaging. In respect to specific benefits, food processors were extremely concerned on the market share and customer response. It caused by management information within manufacturing processes at the level input (breadth) rather than upward or backward tracing. Micro level industries are relatively overestimated on market share and customer response, also, a tremendous costly at the material/labelling. Key words: Food supply chain, firm characteristics, traceability levels, traceability costs, traceability benefits.